The Road Performance Analysis of the Tuah Madani Roundabout, Batam-Indonesia - Yehezkiel Immanuel; Andri Irfan Rifai; Joewono Prasetijo (International Journal Labs, 2022)
Roundabouts are considered to play a role as an effective replacement for signalized intersections and reduce congestion in urban areas. The increase in vehicles each year causes roundabouts to be ineffective in distributing vehicles. This paper aims to analyze road performance. The research method was carried out by means of a field survey. Data was collected from the Tuah Madani Roundabout, Batam, Indonesia. The results show that the average speed is 46 km/hour and a small degree of saturation, with a good level of service. It is stated that the roundabout is still comfortable for motorists to pass through.